Micro-RNA-regulated proangiogenic signaling in arteriovenous loops in patients with combined vascular and soft-tissue reconstructions: revisiting the nutrient flap concept - Henn, Dominic; Abu-Halima, Masood S.; Falkner, Florian; Wermke, Dominik; Meme, Lilian; Kühner, Clemens; Keller, Andreas; Kneser, Ulrich; Meese, Eckart; Schmidt, Volker-Jürgen (Plastic and reconstructive surgery, 2018)
Background:The placement of arteriovenous loops can enable microvascular anastomoses of free flaps when recipient vessels are scarce. In animal models, elevated fluid shear stress in arteriovenous loops promotes neoangiogenesis. Anecdotal reports in patients indicate that vein grafts used in free fl
Publication Date: October 2018
Gesehen am 02.10.2019